Incorporation of metal oxides in electropolymerization of poly(3,4-ethylenedioxythiophene)/graphene oxide for supercapacitor - Azman, Nur Hawa Nabilah (2018)
Supercapacitor is a type of energy storage device which is useful for storing a large amount of energy that can be charged and discharged in short amount of time with long life span. Electrode material which is the most important part of supercapacitor plays an important role in storing a high amount of energy. In this study, composites consisting of poly(3,4-ethylenedioxythiophene) (PEDOT), graphene oxide (GO) and metal oxides were prepared and its supercapacitive performances as electrode materials for supercapacitor were studied. Initially, different applied potentials, concentration of GO and electropolymerization times were studied for the preparation of PEDOT/GO. It was revealed that PEDOT/GO with 1 mg/ml GO electropolymerized for 10 minutes at 1.2 V exhibited the highest specific capacitance. In order to further improve the supercapacitive performance of the composite, metal oxides (MnO2, Fe2O3 and MnO2/Fe2O3) which are recognized for their high specific capacitance were introduced into the optimized PEDOT/GO composite. Various concentrations and the molar ratio of metal oxides precursor were studied to prepare PEDOT/GO/MnO2, PEDOT/GO/Fe2O3 and PEDOT/GO/MnO2/Fe2O3. Raman spectroscopy and Fourier transform infrared (FTIR) spectra revealed the composites were successfully incorporated with metal oxides upon the addition of MnO2, Fe2O3 and MnO2/Fe2O3 into PEDOT/GO. The presence of metal oxides in the PEDOT/GO was further confirmed via X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) measurements and the results displayed all the distinctive peaks of MnO2, Fe2O3 and MnO2/Fe2O3. In addition, from the XRD and XPS, the phases of the metal oxides were also confirmed as MnO2 and Fe2O3 (hematite) with oxidation states of Mn4+ and Fe3+, respectively. The supercapacitive properties of the composites were studied by sandwiching two electrodes together and separated by a filter paper soaked in 1 M KCl. PEDOT/GO/MnO2/Fe2O3 composite exhibited the highest specific capacitance (287 F/g) compared to PEDOT/GO/MnO2 (239 F/g), PEDOT/GO/Fe2O3 (221 F/g) and PEDOT/GO (73 F/g) at 25 mV/s. The MnO2 and Fe2O3 particles were successfully anchored on the wrinkled paper-like sheets of PEDOT/GO as can be seen from FESEM images which acted as spacers in order to improve the supercapacitive performances by maximizing the utilization of electrode materials by the electrolyte ions. The PEDOT/GO/MnO2/Fe2O3 is a suitable candidate for a high-performance supercapacitor due to the synergistic effect provided by the PEDOT, GO, MnO2 and Fe2O3 that help to enhance the performance of the composite for supercapacitor application as revealed from GCD with specific energy and power of 11 Wh/kg and 1900 W/kg at 4 A/g, respectively. The PEDOT/GO/MnO2/Fe2O3 composite also revealed the lowest charge transfer resistance that leads to the superior supercapacitive performances. Thus, PEDOT/GO/MnO2/Fe2O3 composite displayed the highest supercapactive performances compared to PEDOT/GO/MnO2 and PEDOT/GO/Fe2O3.